Analysis of Determinants of Coffe Grower’s Decisions to Participate in Fores and Land Rehabilitation Programs in Lengkiti Sub District, Ogan Komering Ulu District - Karlina, Cynthia; Sjarkowie, Fachrurrozie; Minha, Amruzi (Journal of World Science, 2022)
This study analyzes internal factors (income, expenditure, land area, education, availability of labor, age and location) and external factors (transportation, communication, market, capital). Where internal and external factors can affect the participation of farmers in forest and land rehabilitation programs in Lengkiti District, Ogan Komering Ulu Regency. The approach model in this research is statistical analysis. The data processing in this research uses SPSS 26 with binary logistic regression analysis. The results showed that 120 coffee farmers from the selected sample, it was known that 53 coffee farmers participated in the Forest and Land Rehabilitation Program in Lengkiti District, Ogan Komering Ulu Regency, as many as 67 coffee farmers who did not participate in the Forest and Land Rehabilitation Program in Lengkiti District. Ogan Komering Ulu Regency classified by the model is 55.8%. The variables that affect the participation of farmers in the forest and land rehabilitation program are the income variable (X1) with a sig value of .025, the land area variable (X3) with a sig value. .026, and the location variable with a value of sig. .014.